2003
DOI: 10.1086/378189
|View full text |Cite
|
Sign up to set email alerts
|

When Is a Bulge Not a Bulge? Inner Disks Masquerading as Bulges in NGC 2787 and NGC 3945

Abstract: We present a detailed morphological, photometric, and kinematic analysis of two barred S0 galaxies with large, luminous inner disks inside their bars. We show that these structures, in addition to being geometrically disk-like, have exponential profiles (scale lengths ∼ 300-500 pc) distinct from the central, non-exponential bulges. We also find them to be kinematically disk-like. The inner disk in NGC 2787 has a luminosity roughly twice that of the bulge; but in NGC 3945, the inner disk is almost ten times mor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
95
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(105 citation statements)
references
References 58 publications
8
95
2
Order By: Relevance
“…Its orientation is very similar to that of NGC 4371 (bar ∆PA = 88 • , inclination = 55 • ). Unlike NGC 4371, NGC 3945 also has a small nuclear bar (Erwin et al 2003), which our model does not.…”
Section: Comparison To Ngc 3945contrasting
confidence: 54%
See 2 more Smart Citations
“…Its orientation is very similar to that of NGC 4371 (bar ∆PA = 88 • , inclination = 55 • ). Unlike NGC 4371, NGC 3945 also has a small nuclear bar (Erwin et al 2003), which our model does not.…”
Section: Comparison To Ngc 3945contrasting
confidence: 54%
“…In this Section we compare the simulation to three early-type disc galaxies where previous study has shown the existence of distinct, moderately large NDs and/or massive stellar nuclear rings (which could plausibly be the most visible signature of an extended ND) inside bars (Erwin & Sparke 1999;Erwin et al 2003;Erwin 2004;Nowak et al 2010;Comerón et al 2010). Further details concerning the NDs, including their relation to the central bulges, can be found in Erwin et al (2014).…”
Section: Photometric Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, mergers can create bulges that rotate (e.g., Bekki 2010; Keselman & Nusser 2012), and bars can spin-up classical bulges (e.g., Saha et al 2012;Saha 2015), thus rotation is not a definitive signature of a pseudo-bulge. Furthermore, many galaxies host both a classical and a pseudo-bulge (e.g., Erwin et al 2003Erwin et al , 2015Athanassoula 2005;Gadotti 2009;MacArthur et al 2009;Erwin 2010;dos Anjos & da Silva 2013;Seidel et al 2015). In the recent literature, pseudo-and classical bulges have frequently been divided at the Sérsic index n 2 sph = (e.g., Sani et al 2011;Beifiori et al 2012), although, from a selection of hundreds of disk galaxies imaged in the Kband, Graham & Worley (2008) observed no bimodality in the bulge Sérsic indices about n 2 sph = or any other value.…”
Section: Pseudo-versus Classical Bulgesmentioning
confidence: 99%
“…Many external galaxies have been found to host compound bulges. For instance, Méndez-Abreu et al (2014) found that ∼ 30% of their sample of face-on barred galaxies showed signs of multiple bulge components, while Erwin et al (2015) presented a sample of nine galaxies with composite bulges (see also Erwin et al 2003). Thus, composite bulges are not rare, and it is conceivable that the Milky Way has one too.…”
Section: Introductionmentioning
confidence: 99%